IMPLEMENTATION OF THE GENERAL PRINCIPLES OF GOOD GOVERNANCE IN GOVERNMENT ADMINISTRATION IN WEST JAVA - Taty Sugiarti (PT. Radja Intercontinental Publishing, 2025)
This study examines the implementation of the General Principles of Good Governance in government administration in West Java, with particular emphasis on identifying implementation challenges and formulating recommendations for improvement. The research employs a normative-empirical legal research method by combining an analysis of relevant laws and regulations, legal principles, and administrative law doctrines with an examination of their application in governmental practice. The findings indicate that the implementation of the General Principles of Good Governance in West Java has not been fully effective, as several obstacles remain in translating normative standards into consistent administrative practices. These challenges may affect the quality, accountability, legal certainty, and fairness of government decision-making and administrative actions. Therefore, strengthening the application of good governance principles requires improvements in administrative procedures, institutional capacity, regulatory compliance, and the consistency of public officials in exercising governmental authority. This study recommends strengthening institutional mechanisms and administrative practices to ensure that the General Principles of Good Governance are effectively incorporated into government administration in West Java.